1979
DOI: 10.1084/jem.149.1.267
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylcholine-specific helper T cells in mice with an X-linked defect of antibody production to the same hapten.

Abstract: F1 male mice with the CBA/N X-linked defect that are unable to produce plaque-forming cell responses to phosphorylcholine (PC) provide normal PC-specific helper T-cell activity when compared to F1 female littermates. Inhibition of helper activity with anti-idiotypic antiserum indicates that PC-specific T cells from both NBF1 female and male mice possess predominantly BALB/c myeloma protein HOPC-8 idiotypic determinants. Therefore, the CBA/N defect cannot be explained as a deletion of genes coding for V-region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Although it is possible that this finding is a result of the expression of the CBA/N defect directly at the T-cell level, this seems unlikely for two reasons. First, F1 male T cells have been shown to express T15 idiotype in levels similar to those found in F1 female T cells (20). Second, similar results are obtained using helper T cells from mice depleted of B cells and circulating T15 idiotype by injections of anti-g chain antibody from birth.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Although it is possible that this finding is a result of the expression of the CBA/N defect directly at the T-cell level, this seems unlikely for two reasons. First, F1 male T cells have been shown to express T15 idiotype in levels similar to those found in F1 female T cells (20). Second, similar results are obtained using helper T cells from mice depleted of B cells and circulating T15 idiotype by injections of anti-g chain antibody from birth.…”
Section: Discussionsupporting
confidence: 67%
“…The 30% of T 15 + idiotypic B cells activated would represent the frequency of T 15-positive precursors in the PC-binding B-cell pool. Alternatively, one could argue that F1 males do have a limited number of T15 recognizing helper T cells, whose activity might result from exposure to the T and B cells bearing the T15 idiotype found in these mice (20,21). The helper T cells derived from OVA-primed F1 female mice by themselves elicit very small anti-PC responses.…”
Section: Discussionmentioning
confidence: 99%
“…The 7-day IgG anti-SRBC PFC responses of lethally irradiated Fi mice were measured after immunization with SRBC and reconstitution with anti-theta 4-C-treated spleen cells from normal Fi mice, along with the activated T cells as noted cell function known to be defective in xid mice is the ability of their T cells to augment LPS-induced B-cell activation (Goodman & Weigle 1979). Data indicating that the T cells of CD male mice are unable to support a T-15 predominant anti-PC response (Bottomly & Mosier 1978) have not been confirmed (Kaplan & Quintans 1979, Quintans et al 1981. Further studies are awaited to clarify this issue.…”
Section: Schermentioning
confidence: 99%
“…production, we found in another in vivo experiment that antibody titres to oxazolone were significantly higher in non-infected NK cell-depleted C57Bl/6 mice. In previous experiments investigating the importance of B cell function in S. aureus-induced septic arthritis, Zhao et al [10] have shown that expression of arthritis was less severe in Xid mice, which display disturbances of B cell functions [29], than in healthy controls. As these mice differed from the controls not only by showing lower levels of antibodies to S. aureus-specific antigens, but also in the total levels of immunoglobulin subclasses and as well as in spleen cytokine mRNA expression, it is not possible to point out a single B cell-dependent arthritis accelerating factor present both in the Xid and in our NK cell depletion model.…”
Section: Discussionmentioning
confidence: 99%